Development of Arts and Culture Leadership Enhancement Training Curriculum for Student in Faculty of Arts Education Bunditpatanasilpa Institute - Srisuk, Chinakrit (Arts of Management Journal, 2020)
The purposes of this research were 1) to study basic information and needs for the development of arts and culture leadership enhancement training curriculum; 2) to develop arts and culture leadership enhancement training curriculum for students; and 3) to try out and evaluate the developed arts and culture leadership enhancement training curriculum for students in the Faculty of Arts Education, Bunditpatanasilpa Institute. This study was the three-phase research and development. The research instruments consisted of 1) interview form, 2) survey, 3) arts and culture leadership enhancement training curriculum, 4) pretest, 5) posttest, 6) work assessment scale, 7) Arts and Culture Leadership assessment scale, and 8) attitude towards Arts and Culture Leadership Enhancement Training Curriculum assessment scale. Data were collected, then analyzed using statistics, including percentage, mean, standard deviation, and effectiveness index (E.I.). summarized as follows: 1) The development of arts and culture leadership enhancement training curriculum was important as a mechanism to cultivate all youths in order to conserve, preserve, create, nourish, and disseminate arts and culture as a national identity in various forms at local, national and international levels. 2) The developed arts and culture leadership enhancement training curriculum consisted. In addition, the components of developed training curriculum included 7 components. From the quality assessment by experts, was consistent with the consistence index of 1.0. 3) The effectiveness index (E.I.) of the attendees in the arts and culture leadership enhancement training curriculum was 0.3984, accounting for 39.84%. From Leadership characteristics of students observation form, the overall student presentation was at the highest level. Attendees’ overall arts and culture leadership behavior were at the high level and their opinions towards the developed training curriculum was at the high level